Sewage management needs in Kuantan from 2013 to 2020 - Zuzilawati, Nasir (2014)
Sewage is generated by human activities continuously. As the population increases in the country, the quantities of sewage also increases every year. Many sewage systems were introduced in the country to protect the health of human and environment. From the year 1993, the sewage system in Malaysia has been given to the private management. Now, it is Indah Water Konsortium Sdn. Bhd.'s (IWK) responsibility to manage the sewage systems in the country. This study was conducted to study the sewage management needs in Kuantan from the year 2013 to year 2020. The objectives of this study are to study the sewage management system used in Kuantan through community perception, to identify the problems faced by IWK Kuantan in sewage management and to recommend improvements to the existing sewage management system. The information collected for this study was obtained from IWK and several housing areas in Kuantan. The information included in this study were new and old sewage systems used in Kuantan and how IWK manage the problems in sewage management. As a conclusion, IWK in Kuantan is responsible for improvements to the sewage management in Kuantan. Therefore, IWK should provide personnel on standby during weekends and public holidays to handle any problems that may crop up. Thus, it can provide good quality sewerage and protect the health of both humans and the environment.